UJI AKTIVITAS ANTIBAKTERI SEDIAAN SABUN CAIR MINYAK ATSIRI KULIT BUAH JERUK BALI (Citrus maxima) - Yustisi, Andi Juaella; Wahyuningsih, Sri; Auliah, Nielma (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Pomelofruit (Citrus maxima) has several chemical compounds, one of which is essential oil, 6.68g of essential oil was found in the peel of the pomelofruit (Citrus maxima) which has an active compound, namely limonene (94.96%). The essential oil provided strong antibacterial activity against S. aureus isolates. The purpose of the study was to formulate the essential oil of pomelofruit peel (Citrus maxima) into liquid soap preparations that met physical stability and to test the antibacterial activity of liquid soap preparations of pomelofruit (Citrus maxima) peel essential oil against S. aureus bacteria. The method used in testing the stability of liquid soap preparations is cycling test and in the antibacterial activity test using the Disk diffusion method. The results obtained that the essential oil of pomelofruit peel (Citrus maxima) can be formulated in the form of liquid soap because it meets the physical stability test, namely before and after the cycling test and activity tests. antibacterial against S. aureus. at 1% concentration of 18.9mm (strong), 3% of 20.4mm (very strong), and 5% of 21.1mm (very strong). Based on this, the essential oil of pomelofruit peel (Citrus maxima) can be made into liquid soap preparations that meet the physical stability test and have antibacterial activity in very strong category at a concentration of 5% in inhibiting the growth of S. aureus bacteria.